Relative assessment of psychomotor abilities and selected skills in badminton - Singh, M. (Global journal for research analysis, 2017)
The purpose of the study was to assess the relationship psychomotor abilities in relation to selected sports skill in Badminton. A group of sixty state and national level players from J&K state in northern India were selected purposively to attain the objectives of the study. All the subjects, after having been informed about the objective and protocol of the study, gave their consent and volunteered to participate in this study. Pearson's product moment correlation coefficient technique employed to find out the relationship between selected psychomotor abilities, coordinative abilities and skill related components of fitness with selected sports skill in badminton. The level of p..0.05 was considered significant. It was found that the psychomotor abilities (i.e., Kinesthetic Perception and Speed of Movement) significantly influence the performance of Shot Serve, Clear and smash in Badminton.